Fibropapillomatosis in immature Green Turtles (Chelonia mydas) from the Gulf of Venezuela - Nínive Espinoza-Rodríguez; Héctor Barrios-Garrido (Revista Científica, 2021)
Fibropapillomatosis (FP) is affecting multiple marine turtle (MT) species worldwide. In Venezuela, the understanding about this neoplastic condition is still in early stage. Hence, this paper aims to assess the occurrence and frequency of FP in green turtles (GT) in the Gulf of Venezuela (GV). Herein, it was compiled and analyzed the reports in the database of the NGO ‘Grupo de Trabajo en Tortugas Marinas del Golfo de Venezuela’, which includes all records of stranded MT in the GV from 2000 to 2011. Between 2000 and 2006, in the GV only 2 cases of FP in MT had been reported (1.71 % of total records). Subsequently, between 2008 and 2011, encounters of FP were more frequent; resulting in a total of 7 immature GT (2.93 % of the records) documented showing large masses or skin tumors in various parts of the body. The most affected area of the MT’s body was neck and venous sinus (37.50 %), followed by the anterior flippers (18.75 %), plastron (18.75 %), posterior region (cloaca 18.75 %) and lastly, the eyes (6.25 %). All individuals presented two or more body areas with FP. Although a correlation between the presence of FP and environmental factors observed in the study area was not assessed, the turtles evaluated came from coastal waters with high levels of eutrophication, habitat degradation, and pollution. It is necessary to monitor the occurrence of this disease and the environmental factors that may negatively affect the survival of MT populations in the GV.